Pharmaceutical Compatibility of Non-Sterile Mixing Recipes in Pediatric Patients in Covid-19 Pandemic: Kesesuaian Farmaseutik Resep Racikan Non-Steril Pada Pasien Pediatri dalam Pandemi Covid-19 - Kamri, Andi Maulana; Mirawati, Mirawati; Ningsih, Yuyun S (Universitas Tadulako, 2025)
Background: Drug compounding is the process of combining, mixing, or changing ingredients in the manufacture of drugs to meet patient needs. The risk of pharmaceutical incompatibility can affect the stability and efficacy of the compounded preparation.Objectives: This study aims to determine the pharmaceutical feasibility of non-sterile prescriptions in pediatric outpatients by evaluating dosage forms, concentrations, stability, and potential drug incompatibilities.Materials and Method: This study used a cross-sectional design with a purposive sampling technique and retrospective data collection. The sample in this study was 58 sheets of concoction recipes for children in Pulvere form.Results: The results showed that all prescription dosage forms were powder, and the strength of the drug was fully stated on the prescription. Based on the results of the study, several prescriptions had the potential for instability, including those containing Ambroxol (1.72%), Cetirizine (3.44%), Codeine (1.72%), Dexamethasone (1.72%), Methylprednisolone (3.44%), Isoniazid (1.72%), Metronidazole (5.17%), Nifedipine (1.72%), Omeprazole (1.72%), Paracetamol (5.17%), Prophylthiouracil (3.44%), Ranitidine (3.44%), Rifampicin (1.72%), Salbutamol (10.34%), Triprolidine HCl + Pseudoephedrine HCl (3.44%), Vitamin B complex (1.72%), and Vitamin C (3.44%). Additionally, one prescription contained drugs with potential immiscibility, namely N-acetylcysteine and Erythromycin. The drugs Erythromycin, Salbutamol, and N-acetylcysteine were identified as having the potential for incompatibility.Conclusion: Vitamin C and Vitamin B complex most frequently exhibited hygroscopic instability and photolytic degradation; therefore, it is not recommended to be mixed.